Discover the Diamond in You: The 59 Minute Guide to Success - Arindam Chaudhuri (Vikas Publishing House, 2009)
This one, which you are holding in your hands, I can assure you is a real diamond . . . The 9Ps of success that Arindam so swiftly and lucidly narrates will help you overcome failures and achieve success - because we all need some guidelines when we are down . . . This book is guaranteed to inspire you and it will definitely get you started on your path to discover the diamond within. There is a lifetime of learning squeezed into this innovative book. 59 minutes is all Arindam asks from you and you will have a more positive approach to your life forever. I finished this book in 59 minutes flat and it read like a story I have often lived and experienced. You too will discover a part of yourself in these pages and get inspired. Simple and Realistic ... Empowering and Motivating ... AMITABH BACHCHAN FOREWORD by the Success Icon of Billion Hearts! SHAH RUKH KHAN!!!